Assessing performance of different tillage and nutrient management practices using soil quality index in maize (Zea mays L.)-wheat (Triticum aestivum L.) cropping system - SINHA, NISHANT K.; CHOPRA, USHA KIRAN; SINGH, ANIL KUMAR; KUMAR, NIRMAL; MOHANTY, MANORANJAN; JAYARAMAN, SOMASUNDARAM (Journal of Soil and Water Conservation, 2024)
Assessment of a soil quality index (SQI) is important for determining the degree of sustainability and crop productivity. This study developed several SQI under the maize-wheat crop system (M-W). The most sensitive indicator was identified to assess the impact of different management practices on soil quality. The management practices comprise two tillage and seven integrated nutrient management (INM) systems. The soil physical, chemical and biological parameters were measured, scored and screened through principal component analysis (PCA). The effect of the different management practices on individual soil parameters was also studied. Tillage systems significantly affected (P < 0.05) all the physical and biological properties. Among chemical properties, soil organic carbon (SOC) and nitrate nitrogen (NO3-N) were significantly affected by the tillage treatments. The weighted additive and multiplicative methods were used to calculate the linear additive soil quality index (LASQI), non-linear additive soil quality index (NLASQI), linear multiplicative soil quality index (LMSQI) and non-linear multiplicative soil quality index (NLMSQI). Based on the higher variation explained among treatments, NLMSQI was identified as the most sensitive SQI for all imposed INM in M-W. The NLMSQI indicated higher soil quality with the application of 100% N through organic sources (Org N+ PK) under both tillage systems. Between the tillage systems, NLMSQI indicated the superiority of bed planting (BP) over conventional tillage (CT) in M-W rotation. Results indicated that NLMSQI was positively and significantly correlated with yield of maize (r = 0.84, p < 0.01, n = 21 under BP, r = 0.73, p < 0.0, n = 21 under CT) and wheat (r = 0.75, p < 0.01, n = 21 under BP, r = 0.63, p < 0.01, n = 21 under CT) after five years of experimentation, indicating its practical applicability in soil quality and crop productivity.